STUDI KESIAPAN GURU DAN KETERSEDIAAN SARANA PRASARANA SEKOLAH DALAM PENERAPAN ROBOTIKA EDUKATIF PADA PEMBELAJARAN IPA DI SEKOLAH DASAR - Diska Ayu Saputri; Eka Sastrawati; Issaura Sherly Pamela (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to describe teacher readiness and the availability of school facilities in the implementation of educational robotics in primary school science learning. This research employed a qualitative case study approach, conducted at SD Negeri 42/IV Jambi during the odd semester of the 2025/2026 academic year. Data were collected through interviews, observations, and documentation involving teachers who had attended educational robotics training and the condition of school facilities. The results indicate that teachers possess basic understanding of educational robotics, but their technical skills and ability to plan robotics-based learning are still limited. Teacher readiness is supported by a positive attitude and self-learning efforts, yet the implementation of robotics learning is not optimal due to the absence of robotics kits and devices. Regarding facilities, the school has provided computer laboratories, laptops/Chromebooks, and stable internet access, but robotics devices for practice are not yet available. Educational robotics has the potential to enhance student motivation, understanding of science concepts, as well as critical thinking, creativity, collaboration, and problem-solving skills. The study recommends providing complete robotics kits and further training for teachers to support the effective implementation of educational robotics.